Nesting success on the emergences of Caretta caretta in the island of Boavista (Cape Verde islands, Western Africa) - López, Óscar; Ordi, D. del; Madariaga, Begoña; Díaz Merry, A.; Abella Pérez, Elena; Gracia, M.; Herraiz, L.; Ballell-Valls, Lluis; Borrás, S.; Varo-Cruz, Nuria; Cejudo, Daniel; López-Jurado, Luis Felipe (2017)
The nesting population of loggerhead sea turtle, Caretta caretta, (Linnaeus 1758) in Boavista island (16º 40'N, 25º 55' W, Fig. 1) is being examined in arder to its conservation as well as knowing the most significant aspects of its reproductive biology. Cape Verde Islands represent one of the most important population of Caretta caretta in the North Atlantic (López-Jurado and Andreu 1998, López-Jurado et al. 1999). The main objective of the research is in the one hand, analyzing which places are mostly selected by turtles for emerge. On the other hand, being able to define which zones of the studied beaches are preferably chosen by turtles to nest, based on the relationship between the number of emergences and number of nests laid.